KARAKTERISTIK PERJANJIAN KERJASAMA PADA PERUSAHAAN PT. PERTAMINA (PERSERO) - Lidya Stephanie, Ni Gusti; Westra, I Ketut; Rudy, Dewa Gede (Kertha Desa; Vol. 01, No. 01, Maret 2013)
Gas station business according to Article h frequently results in a long dispute 1(18) of the Cooperation Agreement of Gas Station Business is a work process done by aCorporate Body or an individual who owns and runs a gas station business or onlyowns one gas station.Cooperation Agreements gas station where PT. Pertamina(Persero) as those who produce and sell Fuel Oil, Fuel Special and other products,have been prepared in advance clauses contained in the agreement by reason of theefficiency of the time, effort and expense, and to apply a uniform standard of service allgas stations that sell products PT. Pertamina (Persero).
Keywords: Gas Station, Cooperation Agreement, Pertamina.